Mindfulness and Psychological Distress in Medical Students: Mediating Role of Emotion Regulation - Nawal Qasim, Hina Rana, Rabbia Ashraf (Pakistan Journal of Medical & Health Sciences, 2022)
The research was conducted to assess the medating role of emotion regulation mediate between mindfulness and psychological distress (depression, anxiety, stress). In the current study, correlation research design and purposive sampling was used to collect data from both public and private medical colleges. Sample was comprised of 216 participants (men; n=96; women; n= 120). Mindful Attention Awareness Scale (Brown & Ryan, 2003), Emotion Regulation Questionnaire (Gross & John, 2003), DASS 21 (Lovibond & Lovibond, 1995) along with demographic information sheet were used to assess target study variables. Results were analyzed through SPSS 21. Result showed significant relationship among all variables. Emotion regulation found to play as a mediator role between mindfulness and psychological distress (anxiety). The results of this study help clinical psychologists to devise improved training programs and therapeutic interventions for medical students for minimizing the distress so that medical students become able to perform better in their academic activities. Keywords: Mindfulness; Emotion Regulation; Psychological Distress